Ways to improve the activity of trade services. - Bobokulov Sanjar Bakhronkulovich; Rabbimova Maftuna Mehrid kizi; Amriyeva Shakhzoda Shukhratovna (Genius Publishing Group, 2023)
Along with the development of retail trade in our country, there is a trend of a change in consumer behavior, an increasing trend of buyers' demand for the quality and assortment of goods and the provided trade services. In such conditions, increasing the quality of services provided to customers by offering additional sales services and competing repeat purchases is one of the modern directions of increasing the competitiveness of retail trade
Keywords: Trade services; trade; enterprises; goods